Energy and Emissions Intensity Analysis of Sectors of the Polish Economy in the Years 1996-2015 - Skrzypek , Jurand (Studia Oeconomica Posnaniensia, 2018)
The aim of the paper is to identify basic trends, which occurred in the area of energy intensity and emissions intensity ratios of sectors of the Polish economy in the years 1996-2015. In the research, input-output and statistical methods have been utilized. Main data sources include: Energy statistics, Input-output tables in constant prices from the year 2010 and Statistical yearbook of industry, all published by the Central Statistical Office (GUS). Data have been gathered in a unified database, in the layout of 15 energy sources by 32 sectors (+ households). A database connects the data, organized in a different classification of activities - PKD 2004 and PKD 2007. The conducted research found that the level of energy intensity and emissions intensity ratios of sectors of the Polish economy generally decreased.